Structured Counseling for Auditory Dynamic Range Expansion - Gold, Susan L.; Formby, Craig (Seminars in Hearing, 2017)
A structured counseling protocol is described that, when combined with low-level broadband sound therapy from bilateral sound generators, offers audiologists a new tool for facilitating the expansion of the auditory dynamic range (DR) for loudness. The protocol and its content are specifically designed to address and treat problems that impact hearing-impaired persons who, due to their reduced DRs, may be limited in the use and benefit of amplified sound from hearing aids. The reduced DRs may result from elevated audiometric thresholds and/or reduced sound tolerance as documented by lower-than-normal loudness discomfort levels (LDLs). Accordingly, the counseling protocol is appropriate for challenging and difficult-to-fit persons with sensorineural hearing losses who experience loudness recruitment or hyperacusis. Positive treatment outcomes for individuals with the former and latter conditions are highlighted in this issue by incremental shifts (improvements) in LDL and/or categorical loudness judgments, associated reduced complaints of sound intolerance, and functional improvements in daily communication, speech understanding, and quality of life leading to improved hearing aid benefit, satisfaction, and aided sound quality, posttreatment.
Keywords: Structured counseling; dynamic-range expansion; sensorineural hearing loss; sound therapy.